2020
DOI: 10.1038/s41419-020-03142-0
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation optimized cardiomyocyte phenotype, sarcomere organization and energy metabolism in infarcted heart through FoxO3A-VEGF signaling

Abstract: Vagus nerve stimulation (VNS) restores autonomic balance, suppresses inflammation action and minimizes cardiomyocyte injury. However, little knowledge is known about the VNS’ role in cardiomyocyte phenotype, sarcomere organization, and energy metabolism of infarcted hearts. VNS in vivo and acetylcholine (ACh) in vitro optimized the levels of α/β-MHC and α-Actinin positive sarcomere organization in cardiomyocytes while reducing F-actin assembly of cardiomyocytes. Consistently, ACh improved glucose uptake while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…[ 39 ] In addition, the enhanced expression of FoxO3a markedly abolishes the release of VEGF mediated by protein kinase B (AKT) in cardiomyocytes. [ 46 ] These reports on FoxO3a indicate that it is closely related to increased synthesis of proinflammatory mediators and decreased production of reparative cytokines. In this study, we found that the alternation of FoxO3a phosphorylation is responsible for CCL5‐induced HGF regulation after PHx.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] In addition, the enhanced expression of FoxO3a markedly abolishes the release of VEGF mediated by protein kinase B (AKT) in cardiomyocytes. [ 46 ] These reports on FoxO3a indicate that it is closely related to increased synthesis of proinflammatory mediators and decreased production of reparative cytokines. In this study, we found that the alternation of FoxO3a phosphorylation is responsible for CCL5‐induced HGF regulation after PHx.…”
Section: Discussionmentioning
confidence: 99%
“…Constructions of NFATc1/c2/c4 overexpression adenoviral vectors were prepared as previously described 17 . The gene accession numbers of overexpressing NFATc1/c2/c4 are NM_172390, NM_173091, and NM_004554, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The gene accession numbers of overexpressing NFATc1/c2/c4 are NM_172390, NM_173091, and NM_004554, respectively. Constructions of NFATc3/c4 short hairpin RNA (shRNA) adenoviral vectors were prepared as previously described 17 . These overexpression adenoviral vectors containing Ad-NFATc1, Ad-NFATc2, Ad-shNFATc3 and Ad-shNFATc4 were obtained from Vigenebio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polymorphism rs7240256 (NG_029226.1:g.23449 T > C) in this gene has been reported as a risk factor of VSD. Vascular endothelial growth factor ( VEGF ) plays a key role in morphogenesis of the vascular system and differentiation of endothelial cells [ 11 ]. The human VEGF gene is located on chromosome 6p21.1.…”
Section: Introductionmentioning
confidence: 99%